Coumarin production in Mikania glomerata callus - Pereira, Ana Maria Soares [UNESP]; França, S. C.; Câmara, Francisco Luiz Araújo [UNESP] (My University, 1999)
Cell cultures of Mikania glomerata Sprengel were established with leaf segments cultured on White medium supplemented with 1 mg/L BA and 3 mg/L NAA. Different types and concentrations of growth regulators were tested for callus maintenance. Determination of coumarin content was performed in HPLC using authentic coumarin standard. Growth regulator concentration affected biomass and coumarin accumulation. Cultures developed in semisolid medium containing both BA and NAA exhibited enhanced biomass production as well as coumarin accumulation. In the most favorable conditions tested, cells accumulated 25 μg/g of dry weight what is much inferior to the yield already reported in intact plants (5 mg/g of dry weight). However, results obtained so far suggest several alternatives for culture manipulation in order to optimize the productivity of coumarin by M. glomerata cultured cells.
Keywords: Guaco; Medicinal plant; Mikania glomerata; Tissue culture